Identifying the healthy places to live in Australia with a new environmental quality health index - Shuang Zhou; Zhihu Xu; Wenzhong Huang; Yao Wu; Rongbin Xu; Zhengyu Yang; Pei Yu; Wenhua Yu; Tingting Ye; Bo Wen; Shanshan Li; Yuming Guo (Environment International)
Background: Existing environmental quality indices often fail to account for the varying health impacts of different exposures and exclude socio-economic status indicators (SES). Objectives: To develop and validate a comprehensive Environmental Quality Health Index (EQHI) that integrates multiple environmental exposures and SES to assess mortality risks across Australia. Methods: We combined all-cause, cardiovascular, and respiratory mortality data (2016–2019) from 2,180 Statistical Areas Level 2 with annual mean values of 12 environmental exposures, including PM2.5, ozone, temperature, humidity, normalized difference vegetation index, night light, road and building density, and socioeconomic status. Exposure-mortality relationships were estimated using a spatial age-period-cohort model, and EQHIs (scored 0–100, with higher values indicating better conditions) were constructed. Validation was performed using K-fold cross-validation and spatial regression models. Results: Validation showed strong model performance (R-squared = 83.53 %, 75.55 %, and 52.44 % for EQHI-all cause, EQHI-CVD, and EQHI-Resp). Each interquartile increase in EQHI-all cause reduced all-cause mortality risk by 10 %, with similar reductions for cardiovascular and respiratory mortality. Geographically, EQHIs were higher in south, east, and southeast coastal regions. From 2016 to 2019, SA2s with the highest EQHI (>75) decreased from 27.1 % to 21.1 %. The population weighted EQHI was highest in Hobart and lowest in Darwin. Conclusions: We established, to our knowledge, the first tool to quantify and communicate environmental health risks using three types of mortality data and 12 environmental factors. This EQHI provides a robust framework to assess environmental health risks and guide targeted interventions. Our methodology can be adapted globally to standardize risk evaluation.